Pertumbuhan Tanaman Cabai Rawit (Capsium frutescens L.) Varietas Rajo terhadap Teknik Pemupukan yang di Budidaya secara Monokultur dan Tumpangsari - Mayasari, Eli; Gustiar, F; Ammar, M; Susilawati, Susilawati (Seminar Nasional Lahan Suboptimal, 2022)
Mayasari E, Gustiar F, Ammar M, Susilawati S. 2022. Growth of cayenne pepper (Capsium frutescens L.) rajo variety with fertilization methods by monoculturea and intercropping. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 777-785. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Cayenne pepper (Capsium frutescens L.) is one of the horticultural crops that have economic value, cayenne pepper planted in an optimum environment will produce good plants. One of the important things that need to be considered in the cultivation of cayenne pepper plants is fertilization. Efforts to use vacant land between plants are carried out by planting other plants commonly called intercropping. This study aimed to determine the growth of cayenne pepper (Capsium frutescens L.) rajo variety against fertilization techniques that are cultivated in monoculture and intercropping. This research was carried out with a split plot design consisting of 2 main plots, namely: intercropping and monoculture, which consisted of 4 subplots, namely spot placement, broadcasting, tugal, and spray with 3 replications. The results showed that the fertilization treatment by sowing had an effect on the parameters of plant height, number of leaves, stem diameter, crown diameter, and leaf thickness, both intercropped and monocultured. The growth of cayenne pepper in intercropping is better than that of cayenne pepper grown in monoculture.